PELAKSANAAN KEBIJAKAN KOMUNIKASI ORGANISASI PEMERINTAHAN DI INDONESIA - Purnomo, Arie (Universitas Muhammadiyah Sorong, 2018)
The research aims to know the application policy of organization communication which applied by the government in Indonesia. These research applied to Government in Indonesia. The informant namely has relevant to the task to give policy which must be applied related to the policy of organizational communication. Data analysis which collected it as well as primary and secondary data and further to arrange, to analysis, to interpretation then takes conclusion as the answer to a problem. The result of research showed that organization communication has communicated by a head of an instance and job unit and subordinate it to an application of main task and function with the aim to task by Governor. The application of organization communication it created of organization climate which conducive in vertically, horizontal and diagonal by a leader of the job unit and subordinate in an organization to applied of policy, main task, and function which obligate it. Â